(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Artificial intelligence (AI) is becoming more and more in-built in various facets of our day-to-day lives, particularly social media and online shopping. In India, a nation encountering rapid computerized change, the convergence of Artificial intelligence, virtual entertainment, and web-based business presents the two difficulties and valuable open doors for organizations, buyers, and policymakers. This paper investigates the latest things and future possibilities of artificial intelligence driven developments in web-based entertainment and their impact on online business exercises in the Indian market. Drawing on multidisciplinary research and observational bits of knowledge, we break down the effect of customized proposals, chatbots, opinion investigation, visual hunt, and powerhouse advertising on client encounters, promoting procedures, and plans of action. Furthermore, we talk about the exceptional difficulties and open doors introduced by the Indian setting, including social commerce administrative structures, and security concerns. By looking at the advancing scene of artificial intelligence driven social business in India, this paper means to give significant bits of knowledge to scholastics, specialists, and policymakers trying to comprehend and explore the groundbreaking force of artificial intelligence in molding the destiny of E- business.